Electrochemical pesticide detection with AutoDip – a portable platform for automation of crude sample analyses. Issue 3 (21st November 2014) - Drechsel, Lisa; Schulz, Martin; von Stetten, Felix; Moldovan, Carmen; Zengerle, Roland; Paust, Nils
Abstract : A ball-pen mechanism incorporated into a disposable cartridge mediates dipping of a biosensor into the sample and reagents. Abstract : Lab-on-a-chip devices hold promise for automation of complex workflows from sample to answer with minimal consumption of reagents in portable devices. However, complex, inhomogeneous samples as they occur in environmental or food analysis may block microchannels and thus often cause malfunction of the system. Here we present the novel AutoDip platform which is based on the movement of a solid phase through the reagents and sample instead of transporting a sequence of reagents through a fixed solid phase. A ball-pen mechanism operated by an external actuator automates unit operations such as incubation and washing by consecutively dipping the solid phase into the corresponding liquids. The platform is applied to electrochemical detection of organophosphorus pesticides in real food samples using an acetylcholinesterase (AChE) biosensor. Minimal sample preparation and an integrated reagent pre-storage module hold promise for easy handling of the assay. Detection of the pesticide chlorpyrifos-oxon (CPO) spiked into apple samples at concentrations of 10 −7 M has been demonstrated. This concentration is below the maximum residue level for chlorpyrifos in apples defined by the European Commission.